The Paris Corpus - Aliyah Morgenstern; Christophe Parisse (2012)
The Paris corpus was financed by the Agence Nationale de la Recherche, in the context of two research programmes entitled ‘Acquisition du Langage et Grammaticalisation’ (2005–2008, http://anr-leonard.ens-lsh.fr/ ) and ‘Communication Langagière chez le Jeune Enfant’ (CoLaJE, 2009–2012, http://colaje.risc.cnrs.fr ). The aim of the two programmes was to collect new French data and add five new longitudinal corpora to the international database of the CHILDES project ( http://childes.psy.cmu.edu/ , MacWhinney, 2000), improve researchers’ transcription and coding systems to enable them to study the emergence and development of grammatical patterns used by children between age one and seven, and compare child and adult speech. The programmes brought together specialists from various fields of language acquisition in order to study language development in the same longitudinal corpus from a multimodal and interdisciplinary perspective. The analyses aimed to find regularities in acquisition for each child and across the children.